Peningkatan Pengetahuan dan Wawasan Kepada Anak Sekolah Dasar Dalam Bidang Teknologi Informasi dan Komunikasi - Izzuddin, Ahmad; Tunggal Prasetiyo, Dani Hari; Baihaqi, Mas Ahmad; Hikmah, Nuzul; Ariyanti, Dyah; Aprilia, Ira (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
Quality human resources will bring a nation into a prosperous and prosperous nation. A prosperous and prosperous nation does not escape the technological advances that are controlled. ICT training aims to increase knowledge and insight in the field of computer information technology. This is because in the 4.0 era knowledge and skills in the field of ICT are indispensable. The COVID-19 pandemic that has hit the world and including Indonesia has affected the learning system for children. The learning system that was originally face-to-face was replaced with an online system. This is a new problem. Therefore, efforts are needed to improve skills in the field of ICT in children. From the description that has been presented regarding the skill needs of children, the community service program team took the initiative to do service with the theme of improving ICT skills in children with the target of fifth graders at SDN Tamansari 1. Service activities were carried out with three schemes consisting of preparation, preparation and implementation of activities. Results of activities The results of activities participants understand about the functions and working systems of hardware, basic software work processes and functions of Microsoft office icons. Participants are also taught how to operate a computer and use the available applications and features.